Analisis Dan Perancangan Sistem Informasi Monitoring Dan Evaluasi Anggaran Pendapatan Dan Belanja Daerah (APBD) Pada Dinas Lingkungan Hidup Kota Jambi - Sari, Ira Fitria; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2021)
The Jambi City Environmental Service does not yet have an information system for monitoring and evaluating the regional revenue and expenditure budget (APBD) which can facilitate budget control for activities to be carried out. The process of Monitoring and Evaluation of the Regional Revenue and Expenditure Budget at the Jambi City Environmental Service still relies on the activity control card made by each financial management staff manually, resulting in frequent errors in calculating the realization of budget absorption each month and lack of control from the Technical Implementing Officer. Activities in each sector to control the cash budget that have been planned beforehand, so that there are often delays in budget disbursement. The purpose of this research is to analyze and design an information system for monitoring and evaluation of regional revenue and expenditure budgets in accordance with the needs of the Jambi City Environmental Service. With this information system, the Jambi City Environmental Service can make it easier in terms of budget realization information. Designing the Information System for Monitoring and Evaluation of the Regional Revenue and Expenditure Budget at the Jambi City Environmental Service uses object-based modeling techniques to describe system analysis and design, namely in the form of use case diagrams, activity diagrams, and class diagrams. The output of this research is in the form of a prototype design of the system, Analysis and Design of Information Systems for Monitoring and Evaluation of the Regional Revenue and Expenditure Budget at the Environmental Service of Jambi City. Suggestions for further research in order to complement with other data management, such as reports on the physical realization of disbursed budgets.